Vacuum engineering calculations, formulas, and solved exercises - Berman, A. (Armand) (Academic Press, 1992)
This book was written with two main objectives in mind-to summarize and organize the vast material of vacuum technology in sets of useful formulas, and to provide a collection of worked out exercises showing how to use these formulas for solving technological problems. It is an ideal reference source for those with little time to devote to a full mathematical treatment of the many problems issued in vacuum practice, but who have a working knowledge of the essentials of vacuum technology, elementary physics, and mathematics. This time saving book employs a problem-solving approach throughout, providing the methodology for computing vacuum parameters. References and solved exercises are appended to the end of each chapter. Key Features * Presents the thermal transpiration effect in vacuum gauges with application to capacitance manometers in vacuum metrology * Covers analytical-statistical calculation of conductances of vacuum elements * Examines the molecular flow of gas through short pipes and channels * Explains chocked and nonchocked laminar flow of gas through vacuum elements.